Pemetaan penelitian tentang kartu kredit syariah pada lembaga keuangan syariah: Studi bibliometrik vosviewer literatur review - Abdillah, Mochammad Nizar (Maliki Interdisciplinary Journal, 2024)
Islamic credit cards are products issued by several Islamic banks in Indonesia, but their use is still very minimal among the public. The issuance of this credit card aims to be a tool that makes it easier for the public to make transactions and to provide a sense of security to the public when they carry large amounts of money. This study aims to disseminate information about sharia credit cards to the wider community so that these cards can be used more and more